Theories result from several repeated experiments.
Theories explain observations and hypotheses.
Theories may be revised over time.
Explanation:
Scientific theories are purely explanations into an observation and hypothesis. The are general binding explanations that have been developed from several tests.
- Theories are products of different stages of experiments in their own regard.
- For a theory to be accepted by the scientific community, its hypothesis statement must be:
- Testable
- Repeated
- Falsifiable
- Based on new evidence, a theory may be revised with time. One of such is the Dalton's atomic theory with a modern atomic theory version now.
Learn more:
Experiments brainly.com/question/5096428
#learnwithBrainly
Gravitational potential energy =
(mass) x (gravity) x (height)
= (5.8 kg) x (9.8 m/s²) x (2.5 m)
= 142.1 Joules (C)
During upward projection the final velocity is zero, and the gravitational acceleration is -10 m/s² (against the gravity).
Therefore; using the equation;
S = 1/2gt² + ut
Where s is the height h, g is gravitational acceleration, and t is the time and u is the initial velocity u, is 16 ft/s.
Thus; h= 1/2(-10)t² + 16t
We get; h = -5t² + 16t
Therefore; the quadratic equation is 5t² - 16t + h =0
Answer:
Vb = k Q / r r <R
Vb = k q / R³ (R² - r²) r >R
Explanation:
The electic potential is defined by
ΔV = - ∫ E .ds
We calculate the potential in the line of the electric pipe, therefore the scalar product reduces the algebraic product
VB - VA = - ∫ E dr
Let's substitute every equation they give us and we find out
r> R
Va = - ∫ (k Q / r²) dr
-Va = - k Q (- 1 / r)
We evaluate with it Va = 0 for r = infinity
Vb = k Q / r r <R
We perform the calculation of the power with the expression of the electric field that they give us
Vb = - int (kQ / R3 r) dr
We integrate and evaluate from the starting point r = R to the final point r <R
Vb = ∫kq / R³ r dr
Vb = k q / R³ (R² - r²)
This is the electric field in the whole space, the places of interest are r = 0, r = R and r = infinity
Answer:
588 N
Explanation:
Since the 60 kg is moving at a constant velocity there is no acceleration. In order for the system to be balanced, both the normal force and the force of gravity must be equal. In this case the man has a mass of 60 kg. So to find the force you multiply mass by gravitys constant (9.81). And you end up with an answer of 588.6 but I rounded to 588.